2021
DOI: 10.1093/mnras/stab2869
|View full text |Cite
|
Sign up to set email alerts
|

The Cosmic Ultraviolet Baryon Survey (CUBS) – IV. The complex multiphase circumgalactic medium as revealed by partial Lyman limit systems

Abstract: We present a detailed study of two partial Lyman limit systems (pLLSs) of neutral hydrogen column density NH I ≈ (1 − 3) × 1016 cm−2 discovered at z = 0.5 in the Cosmic Ultraviolet Baryon Survey (CUBS). Available far-ultraviolet spectra from the Hubble Space Telescope Cosmic Origins Spectrograph and optical echelle spectra from MIKE on the Magellan Telescopes enable a comprehensive ionization analysis of diffuse circumgalactic gas based on resolved kinematics and abundance ratios of atomic species spanning fiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 97 publications
2
26
0
Order By: Relevance
“…Several empirical studies at both low and high redshifts have shown that SLFSs, pLLSs, and LLSs have properties that are consistent with the gas being predominantly photoionized (Prochaska 1999;Lehner et al 2013;2016;Prochaska et al 2017b;CCCI;CCCII;Crighton et al 2013;Fumagalli et al 2016b;Cooper et al 2021;Zahedy et al 2021). In Section 4.2, we show that the KODIAQ-Z absorbers have temperatures on average T  4 × 10 4 K, consistent with the gas being photoionized (the same result was found for the low-redshift absorbers with similar N H I ; CCCI).…”
Section: Motivations For Photoionization Modelingsupporting
confidence: 82%
See 1 more Smart Citation
“…Several empirical studies at both low and high redshifts have shown that SLFSs, pLLSs, and LLSs have properties that are consistent with the gas being predominantly photoionized (Prochaska 1999;Lehner et al 2013;2016;Prochaska et al 2017b;CCCI;CCCII;Crighton et al 2013;Fumagalli et al 2016b;Cooper et al 2021;Zahedy et al 2021). In Section 4.2, we show that the KODIAQ-Z absorbers have temperatures on average T  4 × 10 4 K, consistent with the gas being photoionized (the same result was found for the low-redshift absorbers with similar N H I ; CCCI).…”
Section: Motivations For Photoionization Modelingsupporting
confidence: 82%
“…While pLLSs and LLSs have been found often in the CGM of galaxies at both low and high redshift (e.g., Lehner et al 2009Lehner et al , 2013Ribaudo et al 2011;Kacprzak et al 2012;Prochaska et al 2017b;Cooper et al 2021;Berg et al 2022), there is growing evidence that at least some of the pLLSs and LLSs with very low metallicities may probe the denser IGM (very low metallicity being [X/H]  −1.4 at z  1, Berg et al 2022; and [X/H]  −3 at 2  z  3.5, Fumagalli et al 2011aFumagalli et al , 2016aCrighton et al 2016;Lofthouse et al 2020). 13 Recent high-resolution zoom-in cosmological simulations also show that metal-poor ([X/H] < − 3) LLS-like absorbers can be found in the IGM far from any galaxies (Mandelker et al 2019(Mandelker et al , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 17, we update Figure 9 of L13, showing the projected distances between absorbers and their counterpart galaxies over a range of H I column densities from pLLSs to DLAs. We plot the closest galaxy in ρ identified in the field for the absorbers in Hamanowicz et al (2020), the CUBS survey (Chen et al 2020;Cooper et al 2021), and those compiled in L13 (see references therein) along with the MPGs identified for our BASIC-IFU sample. 44 As noted by L13 (but now with a factor ≈2 larger number of galaxy-absorber pairs), there is a clear decrease of the impact parameter with increasing N(H I).…”
Section: Preamblementioning
confidence: 99%
“…The CGM contains a significant fraction of all the met-als created in stars, and the distribution and physical state of this enriched gas can provide constraints on energetic feedback in galaxies (Tumlinson et al 2011;Peeples et al 2014;Oppenheimer et al 2016;Rudie et al 2019). Metal-bearing gaseous structures in the IGM and CGM at z ∼ 2 − 3 appear to be very small ( 100 pc; Rauch et al 2001;Rudie et al 2019), and there are significant variations in the metal content and abundance pattern of the CGM of single galaxies (Zahedy et al 2019(Zahedy et al , 2021Cooper et al 2021), suggesting that metals are often poorly mixed in the gas around galaxies. Future studies comparing the composition of the CGM with other components of the galaxy, including the ISM and stars, will offer critical insight into the baryonic flows that profoundly shape the evolution of galaxies.…”
Section: Constraints On Gas Flowsmentioning
confidence: 99%